2016
DOI: 10.1016/j.jpainsymman.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

A 10-Year Longitudinal Study of Effects of a Multifaceted Residency Spiritual Care Curriculum: Clinical Ability, Professional Formation, End of Life, and Culture

Abstract: A longitudinal, multifaceted residency SC curriculum can have lasting positive effects on physicians' SC skills and their professional/personal formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 42 publications
0
40
0
1
Order By: Relevance
“…Several recent studies reporting on educational programs for healthcare providers (Baldacchino, 2015; Heydark et al , 2017; Marom, 2015; Paal et al , 2015; van de Geer et al , 2017; Vlasblom et al , 2011; Zollfrank et al , 2015) and students (Anandarajah et al , 2016; Mitchell et al , 2006, 2016) included an element designed to help participants understand and articulate their spiritual approach and attend to their own spiritual needs. A few of these studies also report on the effect this training had on patient care, including an increase in spiritual care provision (van de Geer et al , 2017; Zollfrank et al , 2015) and in spiritual screening and making referrals to the spiritual care provider (Vlasblom et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies reporting on educational programs for healthcare providers (Baldacchino, 2015; Heydark et al , 2017; Marom, 2015; Paal et al , 2015; van de Geer et al , 2017; Vlasblom et al , 2011; Zollfrank et al , 2015) and students (Anandarajah et al , 2016; Mitchell et al , 2006, 2016) included an element designed to help participants understand and articulate their spiritual approach and attend to their own spiritual needs. A few of these studies also report on the effect this training had on patient care, including an increase in spiritual care provision (van de Geer et al , 2017; Zollfrank et al , 2015) and in spiritual screening and making referrals to the spiritual care provider (Vlasblom et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, self-reported spirituality had a significant impact on staff attitudes toward spiritual care, but did not demonstrably affect their spiritual care provision in practice. Training programs designed to expand and improve staff spiritual care provision have increasingly included elements that aim to engage participants with their own spirituality and demystify this element of the human experience (Anandarajah et al , 2016; Baldacchino, 2015; Heydari et al , 2017; Mitchell et al , 2016; Paal et al , 2015; Vlasblom et al , 2011; Zollfrank et al , 2015). A few of these programs measured their impact on patient care and found that they led to an increase in staff spiritual care provision (Van de Geer et al , 2017; Vlasblom et al , 2011; Zollfrank et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“… 4 31 35 36 63 A longitudinal study found that while skill-related barriers to discussing SR issues decreased with time and training, structural barriers such as time remained. 35 Other commonly mentioned barriers included concern about offending patients, insufficient training/knowledge, general discomfort and disapproval by peers. 4 31 35 36 63 …”
Section: Resultsmentioning
confidence: 99%
“…The majority of residents lacked knowledge on the SR-related concerns of patients, 28 the role of clergy/clinical chaplains 28 35 45 56 and the availability of spiritual assessment tools. 35 36 When asked, residents were not satisfied with their current knowledge and skills regarding spirituality, 41 with approximately 50% of residents feeling inadequately trained to address the SR-related issues of patients. 4 63 In addition, residents varied widely in terms of the level of comfort and self-reported competency in addressing SR-related care issues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation